Grain‐Size Control on Detrital Zircon Cycloprovenance in the Late Paleozoic Paradox and Eagle Basins, USA. Issue 7 (6th July 2020) - Leary, Ryan J.; Smith, M. Elliot; Umhoefer, Paul
Abstract: Detrital zircon U‐Pb data are routinely used to assess provenance in sedimentary systems. However, recent studies have suggested that zircon provenance interpretation may be biased by grain‐size‐dependent selective transport and deposition. In this study, we present zircon grain‐size and U‐Pb data from 11 sandstone and 11 mudstone samples from the late Paleozoic Eagle and Paradox basins to test whether apparent provenance changes between sandstone and mudstone samples can be explained by changes in zircon grain‐size alone. The Eagle and Paradox basins formed in association with the Ancestral Rocky Mountains (ARM). These basins provide an excellent system to test grain‐size/provenance relationships because they are filled with cyclic stratigraphy that records, via grain size and facies changes, flooding/exposure driven by interglacial/glacial cycles. These cycles are interpreted to have substantially altered sediment transport pathways and provenance of ARM‐related sedimentary rocks. Data presented here suggest that although zircon grain size does correlate to sample grain size in most samples, age spectra appear to be independent of grain size. As such, differences in age spectra between sandstone and mudstone samples appear to be the result of changes in relative inputs of two endmember sources: (1) grains eroded from adjacent basement‐cored ARM uplifts and (2) far‐traveled sediment sourced from outside the ARM system. The data presented in this study also provide a successful proof‐of‐concept test for a manual method of determining zircon grain size. This method is simple and straightforward and can be applied to any sample analyzed using the Chromium off‐line targeting software. Key Points: Detrital zircon age spectra, grain size, and sample grain size are correlated, but this does not affect provenance interpretations We present a simple method for quantifying grain size in detrital zircon samples